ECO- FRIENDLY BIOPOLYMERS AS ADHESIVES – AN OVERVIEW - S. JENNYANGEL; R. DHANDAPANI (International Journal of Pharma and Bio Sciences, 2013)
Over the past 25 years significant advances have been made in the development of different biodegradable polymers. These polymers are eco-friendly and can be tailor-made to a variety of forms like films, sheets, resins, adhesives and waxes. With increasing environmental concerns and need for advancement in medical technologies, biodegradable polymers have been developed to tackle such problems. The natural biopolymers (e.g., starch, cellulose and soy protein) extracted from plants or animal tissues were used for various industrial purposes. Several synthetic polymers of biodegradable and biocompatible nature have been extensively used in the medical sector such as surgical sutures, drug delivery systems, internal fixation devices, and tissue engineering scaffolds. This review summarizes on biodegradable polymers used as adhesives in both industrial and medical applications. In a broader aspect, biodegradable polymers play a dual role as potential solution to waste management and best sealing agent for various applications.